Pemberdayaan Kelompok Tani Oelat’fob melalui Inovasi Teknologi Pertanian di Desa Salbait, Kabupaten Timor Tengah Selatan - Nenotek, Petronella S; Simamora, Agnes V; Bako, Peters O; Nahas, Agustina E; Hahuly, Mayavira V; Kana, Limen Aser; Rihi, Tereza. A Muda; Kanni, Yuannanda Bhoko; Sanam, Jibrael; Folla, Delton Yuandri; Base, Theodosius Lau (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This Community Partnership Program (PKM) aims to empower the Oelat’fo Farmer Group in Salbait Village through the implementation of appropriate agricultural techonology innovations based on local resources. The main issues addressed include small-scale cultivation, manual irrigation, limited knowledge of organic fertilizer production, and restricted market access. The activities include the establishment of a 50–are demonstration plot, the application of drip irrigation, the production of bokashi fertilizer using local materials with Trichoderma sp and mycorrhiza, the construction of fruit fly traps, and digital marketing training. The outcomes of the program indicate an improvement in farmers’ capacity to manage farmland and agricultural techonologies. Approximately 60% of farmers were able to independently produce bokashi fertilizer, 30% were able to install drip irrigation systems, and independently produce bokashi fertilizer, 30% were able to install drip irrigation systems, and 70% perceived the drip irrigation techonology as efficient in terms of water and labor use. The program has contributed to enhancing productivity, efficiency, and farmer’s self-reliance toward sustainable agriculture.